Employee incentives towards corporate reputation / Nur Athirah A. Aziz and Nur Farahani Mohd Romli - A. Aziz, Nur Athirah; Mohd Romli, Nur Farahani (2017)
Corporate reputation is basically the perception that the public have towards the corporate body. Many organization or corporation are trying to build good reputation that can help their organization to gain favourable position in the society that exceed other competitors which also help them in gaining high financial performance. In order to achieve such a positive reputation, the organization is said to actually depend on their employee to be the ambassador for the company and show it to public. Thus, the organization need to ensure that the employee’s satisfaction is achieved so that, they can engaged positively with the organization and one of the way is through giving the incentives to the employee. When the employee is satisfied and engaged positively with the organization, they will help in building good corporate reputation for the organization. It is shown that the employee incentives have a direct relationship with corporate reputation.